Milly, Molly and the stowaways - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2023)
Milly and Molly learns that everyone has a talent and everyone needs to have a sense of worth. Includes teaching guide. Suggested level: junior